Chinese economic presence in East Africa: the case of Kenya - K. A. Gemueva (Vestnik MGIMO-Universiteta)
The first ever Russia-Africa Summit and Economic Forum in October 2019 demonstrates not only interest of both sides in developing bilateral cooperation, but also has every chance of becoming a turning point in translating words into action. Due to advantageous geographical position, dynamic economic development and its role as a transport, logistics and financial center in East Africa, Kenya is justifiably considers as an "entry point" to the African market for foreign companies. At present, Russia's economic presence in this country is extremely limited, and therefore, when developing an effective strategy for promoting the market in Kenya, it seems advisable to study the practical experience of other major players, both to find "keys to success" and to identify potential risks. Russia's economic presence in the country has been very limited so far, thereby learning from the practical experience of other major players would be useful for developing an effective strategy to enter the Kenyan market, both to find "keys to success" and to identify potential risks. The reason why the Chinese experience was chosen as the subject of study is the China's rapid uptake to become  one of Kenya's key partners. Thus, the purpose of this study is to develop recommendations for Russian companies to enter the African market based on the experience of the Chinese economic presence in Kenya.The article analyzes in detail three key areas of Chinese economic activity in Kenya, i.e. foreign trade, infrastructure development and credit financing, as well as linkages between them. The author argues that the willingness of China to implement projects that are in line with the current Kenya`s development agenda was an important factor in the large-scale increase of cooperation. Thus, China's activities are not only aimed at stimulating the export of Chinese goods and services, as well as increasing its geopolitical weight in the region, but also are supporting for Kenya's industrialization, modern and reliable infrastructure development. The Mombasa-Nairobi railway, the largest project involving Chinese companies in Kenya, is used as an example with regard to typical problems that foreign companies may face in Kenya, including media pressure. Based on the analysis of current trends, the author concludes that the further development of bilateral cooperation will depend to a great extent on the commitment from both sides to gradually change the priority areas of cooperation and to use new tools and mechanisms of interaction.